An autopsy‐based study of Trypanosoma cruzi persistence in organs of chronic chagasic patients and its relevance for transplantation. Issue 6 (25th October 2017) - Benvenuti, Luiz A.; Roggério, Alessandra; Cavalcanti, Marta M.; Nishiya, Anna S.; Levi, José E.
Abstract: Background: Chagas' disease (CD) is caused by infection with the protozoan Trypanosoma cruzi . The disease can affect the heart and/or the gastrointestinal (GI) tract, but around 70% of infected individuals remain asymptomatic in the chronic form. Organ transplantation from T. cruzi ‐infected donors is often avoided because of the risk of disease transmission, previously reported after heart, kidney, or liver transplantation. Methods: We investigated by histology, immunohistochemistry, and polymerase chain reaction (PCR) the persistence of T. cruzi in samples of the heart, lung, liver, kidney, pancreas, adrenal gland, esophagus, and GI tract of 21 chronic chagasic patients. Results: Parasite persistence was detected in 12/21 (57.1%) heart samples, mainly by PCR‐based assays. T. cruzi parasites were detected by histology and immunohistochemistry in smooth muscle cells of the central vein from 1/21 (4.8%) adrenal gland samples. No samples of the lung, liver, kidney, pancreas, esophagus, or GI tract were found to have parasites by histology, immunohistochemistry, or PCR. Conclusions: We concluded that, aside from the heart, the other solid organs of T. cruzi ‐infected donors can be used for transplantation with a lot of caution. Such organs are not safe in the view of previous reports of CD transmission, but seem to present a low T. cruzi load compared to the heart.